(untitled) (Journal of the College of Basic Education, 2023)
It is no secret that the linguistic problem is one of the most prominent problems of our cultural life. The people of this age do not have anything to help them with correct reading or correct expression (Al-Azzawi 108/2004), so students graduate from universities and institutes and do not have the ability to write a small article in a sound Arabic language (Bint Al-Shati 191/1971). And the Arabic language began to suffer from a poor level of specialized and professional preparation for its teachers, in addition to the obvious lack of programs offered in the various colleges that prepare teachers of the Arabic language. (Younes 1981/5)As a result, the complaint rose about the weakness of students in all stages of education regarding Arabic grammar, and their inability to understand it and benefit from its rules in evaluating their conversations and writings (Ahmed 169/1979), and the rules of grammar became the burden that school and university students alike bear and complain about (Abu Mughali 1986/ 107), and this is a problem and a long time, and the minds are puzzled in searching for its cause and pointing to the places of the disease in it, so the level decline increases day after day, as if we are in front of a well whose water is gradually depleted and nothing to supply it and fix it (Abdul Tawab 1987/413).